2010
DOI: 10.1097/dbp.0b013e3181dbadc7
|View full text |Cite
|
Sign up to set email alerts
|

Examining Depressive Symptoms and Use of Counseling in the Past Year Among Filipino and Non-Hispanic White Adolescents in California

Abstract: Objective We compared measures of depressive symptoms and use of counseling in the past year for Filipino versus non-Hispanic white adolescents in California. Methods This cross-sectional study used data from 4421 adolescents who completed the 2003 and 2005 California Health Interview Survey. Bivariate analyses, linear regression, and logistic regression were performed. Results Compared to non-Hispanic white adolescents, Filipino adolescents had higher mean 8-item version of Center for Epidemiologic Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Song et al found that female gender was associated with depressed mood among female Asian high school students, 34 Chen et al and Juang et al found that Chinese adolescent females had higher levels of depressive symptoms than males, 31,35 Javier et al found that Filipino females reported higher levels of depressive symptomology than males, 36 and Williams et al found an association between female gender and depressive symptoms among Japanese American adolescents. 37 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al found that female gender was associated with depressed mood among female Asian high school students, 34 Chen et al and Juang et al found that Chinese adolescent females had higher levels of depressive symptoms than males, 31,35 Javier et al found that Filipino females reported higher levels of depressive symptomology than males, 36 and Williams et al found an association between female gender and depressive symptoms among Japanese American adolescents. 37 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 99%
“…71 4) Family economic strain: Javier et al found that lower parental education and living in a single parent household were positively associated with depression among Filipinos. 36 …”
Section: Question 3: Are There Social And/or Cultural Factors That Comentioning
confidence: 99%
“…Filipino youths have a disproportionately heavy burden of behavioral problems, including higher rates of high school drop-out, depression, teen pregnancy, and substance use, compared with whites and other Asian subgroups. However, they are less likely to participate in mental health and preventive care interventions (6) and have significant mental health risk factors, including exposure to harsh parental discipline and parents who have their own high levels of unmet mental health needs (7). Barriers to help-seeking include 1) an intergenerational gap between Filipino parents and children and 2) cultural factors such as Filipinos’ tendency to passively accept the way things are ( bahala na ), to avoid shame ( hiya ) related to accessing mental health services, and to put the needs of family above personal desires (8–11).…”
Section: Introductionmentioning
confidence: 99%
“…U.S.-born Filipino youth exhibit higher rates of behavioral health problems, such as substance abuse, depression, and suicide ideation; as well as for high risk behaviors resulting in elevated rates of adolescent pregnancy and HIV/AIDS infections (Javier et al, 2007; Javier, Lahiff, Ferrer, & Huffman, 2010). U.S.-born Filipino youth also attain significantly lower levels of education than their Philippine-born counterparts and other U.S.-born Asian American youth (Ogilvie, 2008).…”
mentioning
confidence: 99%